Da fenomenologia às ciências cognitivas: o hábito como operador cognitivo - Gala, Adelino de Castro Oliveira Simões (2012)
This dissertation aims at researching the concepts of habit that emerged in philosophy, and then introduce it in the Cognitive Science program through a nondualistic approach. After discussions on methodologies and the researcher´s motivations, the first chapter starts with a survey of the most important philosophers from medieval philosophy that dealt with the theme: Aristotle, Thomas de Aquinas and mainly Duns Scotus. After exploring and identifying the concepts of intentionality and habit, it advances to the twentieth century philosophy into Husserl´s studies, who is recognized as the founder of phenomenology. Afterwards, in order to seek for an alternative to the dualism that underlies Husserl´s research of mind, chapter two engages in the understanding of Merleau-Ponty´s works and mainly his phenomenology of perception. The next step is to link M-Ponty´s philosophy and the Cognitive Science program. This is done in chapter three which contextualizes Varela´s research and how it constrains both fields. Finally, the conclusion suggests a definition of the concept of habit as a cognitive operator, and shows possible future paths for the present work